Troubled Worker Militancy: Challenges Confronting Western Industrial Relations - Barkin, Solomon (Relations industrielles / Industrial Relations, 1983)
This paper presents some thoughts on the development of Western industrial relations Systems since the postwar years and dwells on the questions the unions are now facing.